2020
DOI: 10.1038/s41419-020-02952-6
|View full text |Cite
|
Sign up to set email alerts
|

A miR-210-3p regulon that controls the Warburg effect by modulating HIF-1α and p53 activity in triple-negative breast cancer

Abstract: Reprogrammed energy metabolism, especially the Warburg effect (aerobic glycolysis), is an emerging hallmark of cancer. Different from other breast cancer subtypes, triple-negative breast cancer (TNBC) exhibits high metabolic remodeling, increased aggressiveness and lack of targeted therapies. MicroRNAs (miRNA) are essential to TNBC malignant phenotypes. However, little is known about the contribution of miRNA to aerobic glycolysis in TNBC. Through an integrated analysis and functional verification, we reported… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
49
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(59 citation statements)
references
References 38 publications
(46 reference statements)
1
49
0
Order By: Relevance
“…It has been shown that cancer cells prefer glycolysis as their energy source instead of OXPHOS, even in the presence of oxygen. Certain molecules like HIFs are essential to the survival of cancer cells in a hypoxic environment as transcriptional regulators of aerobic glycolysis 42 , 43 . The activation of HIFs in cancer can cause complex reprogramming of energy metabolism, including mitochondrial oxidative metabolism, glucose catabolism, glucose uptake, and energy production 18 .…”
Section: Role Of Hifs In Tumor Progressionmentioning
confidence: 99%
“…It has been shown that cancer cells prefer glycolysis as their energy source instead of OXPHOS, even in the presence of oxygen. Certain molecules like HIFs are essential to the survival of cancer cells in a hypoxic environment as transcriptional regulators of aerobic glycolysis 42 , 43 . The activation of HIFs in cancer can cause complex reprogramming of energy metabolism, including mitochondrial oxidative metabolism, glucose catabolism, glucose uptake, and energy production 18 .…”
Section: Role Of Hifs In Tumor Progressionmentioning
confidence: 99%
“…When comparing the remaining potential miRNAs, according to the present bioinformatics analysis (miR-93-5p, miR-23c, miR-210-3p, miR-221-3p, and miR-592), all were suggested with important roles in PC screening [61], aggressiveness [8,62,63], and recurrence [7,18,64], or even new etiological values [65] were suggested. These miRNAs have also been highlighted with carcinogenic effects in other tumors, such as endometrial [66,67], osteosarcoma [68], hepatocellular [69], renal [17,70], or colorectal [71], among others [72][73][74]. According to our experimental analysis, miR-210-3p, miR-23c, and miR-592 were suggested as aggressiveness biomarkers in PC and miR-93-5p, miR-130b, and miR-141 were suggested as diagnostic biomarkers for this tumor.…”
Section: Discussionmentioning
confidence: 62%
“…It was demonstrated that miR-210 targets the electron transport chain through SDHD (succinate dehydrogenase complex, subunit D), inducing accumulation of succinate that, in turn, inhibits Prolyl hydroxylase domain enzymes (PHD) and stabilizes HIF-1α, thus forming a positive-autoregulatory loop [ 125 ]. More recently, Du et al demonstrated that miR-210-3p targets GPD1L (glycerol-3-phosphate dehydrogenase 1-like) and consequently affects HIF1α stability inducing an effect similar to that observed with SDHD inhibition [ 61 ].…”
Section: Feedback Loops Between Hif and The Hypoxia-induced Non-comentioning
confidence: 98%
“…Recently, an interesting manuscript of Du et al demonstrated that hypoxia-induced miR-210-3p controls cell proliferation by promoting Warburg effects and, concomitantly by inhibiting p53 activity in triple-negative breast cancer [ 61 ].…”
Section: The Hypoxia-induced Non-coding Rnasmentioning
confidence: 99%